A STUDY ON FACTORS INFLUENCING INVESTMENT DECISIONS OF MIDDLE-INCOME GROUP INVESTORS (International Journal of Food and Nutritional Sciences, 2022)
Investment decisions have a significant impact on people's financial stability, particularly for middle-class people who confront particular financial opportunities and constraints. This study examines the factors that impact the investment decisions of middle-income investors, focusing on their preferences, risk tolerance, financial literacy, and external influences. The study evaluated the investment behavior of this group using a quantitative approach and a sample size of 180 respondents. The findings have significant ramifications for financial advisors, regulators, and investment product developers as they reveal crucial elements including financial objectives, risk perception, and market awareness..